WOMEN IN CANADIAN LITERATURE (Author: M. G. McClung) - Grace, Sherill E. (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1978)
M. G. McClung. WOMEN IN CANADIAN LITERATURE. Toronto: Fitzhenry & Whiteside Limited, 1977. 96 pp. $4.95.